Overview of results in the application of flywheel hybrid transportation systems - Tarraf Mokhammad; V. V. Gayevskiy; Deeb Mukhammad (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
Among several typical energy storage methods, that flywheel energy storage has advantages such as high instantaneous power, high-performance and long service life, making it perfect secondary energy storage technology for traditional internal combustion engine vehicles. Although some progress has been made in the applied research of flywheel energy storage technology, there are no detailed studies at home and abroad that summarize its application in the vehicle applications. This paper searches the data on «flywheel energy storage», analyzes the research progress of flywheel energy storage in automotive industry, and analyzes the research progress of flywheel energy storage in vehicle applications. The search data show that flywheel energy storage technology for the vehicle applications has been studied for the last 20 years, although it is a niche research area. With respect to two typical flywheel hybrid systems, namely electric and mechanical drive, we have focused on the history of the study, research and validation of mechanical flywheel hybrid system in the automotive industry, as well as the structural characteristics of this system, the current state of research and future research trends.